A comparison of high temperature corrosion behaviour between uncoated, Ni-Cr-Mo and Ni-Cr-Al-Y coated 316 stainless steel in ZnCl2-KCl environment - Pooja Mangaladevi; V. Vijeesh; K.S. Ravishankar; Vasudeva Madav (Results in Engineering)
High-temperature corrosion poses a significant challenge to the longevity and performance of materials in extreme environments. This study investigates the corrosion behavior of coated and uncoated 316 stainless steel (SS) in ZnCl2-KCl eutectic molten salt vapor at 600 °C. Contrary to expectations, the results indicate that uncoated 316 SS exhibits lesser corrosion compared to certain coated samples over prolonged exposure. Comprehensive analysis, including weight change measurements, electrochemical evaluations, and surface morphology examination, reveals the degradation mechanisms and the efficacy of coatings. Amongst the various materials used for study, NiCrMo coated 316SS showed least corrosion rate of 8.34 mpy and 3.2 mpy after 20 h and 100 h respectively. The findings provide insights into optimizing material protection strategies in harsh chloride containing molten salt environments.